Sleep Disturbances in Pediatric Bipolar Disorder: A Comparison between Bipolar I and Bipolar NOS - Baroni, Argelinda (Frontiers Research Foundation, 2012)
Introduction: The diagnosis of bipolar disorder (BD) in youths has been controversial, especially for the subtype BD not otherwise specified (BD-NOS). In spite of growing evidence that sleep is a core feature of BD, few studies characterize and compare sleep disturbances in youth with BD type I (BD-I) and BD-NOS. Sleep disturbances are frequently reported in clinical descriptions of children and adolescents with BD, however the reporting of the frequency and characteristics of sleep symptoms in youth with BD-NOS and BD-I during episodes remain poor. This study compares symptom of sleep disturbance as occurring in manic and depressive episodes in BD-I and BD-NOS youth using Kiddie-schedule for affective disorders and schizophrenia, present and lifetime version (K-SADS-PL) interview data. The study also addresses whether symptoms of sleep disturbance vary in different age groups. Materials and Methods: The sample consisted of 70 children and adolescent outpatients at an urban specialty clinic (42M/28F, 10.8 ± 3.6 years old) including 24 BD-I and 46 BD-NOS assessed using K-SADS-PL-parent interview. Results: Sleep disturbances including insomnia and decreased need for sleep were reported by 84.3% of the sample. Enuresis was diagnosed in 27% of sample. There were no significant differences in frequency of sleep symptoms between BD-I and BD-NOS. Regardless of BD subtype, current functioning was negatively correlated with decreased need for sleep but not insomnia, and regardless of BD subtype. Conclusion: The majority of youth with BD presents with sleep symptoms during mood episodes. BD-NOS presents with the same proportion of sleep symptoms as BD-I in our sample.